2023
DOI: 10.1111/joor.13568
|View full text |Cite
|
Sign up to set email alerts
|

Isometric tongue endurance and incomplete laryngeal vestibule closure in Parkinson's disease

Flavia Pereira da Costa,
Raphael Fernandes Casseb,
Daniella Priscila de Lima
et al.

Abstract: BackgroundDysphagia is a common symptom of Parkinson's disease (PD). A delay in laryngeal vestibule closure (LVC) and a reduction in tongue pressure, may affect swallowing safety and increase the risk of pulmonary aspiration.ObjectiveTo verify the relationship between tongue pressure and airway protection in PD patients: (1) comparing tongue pressure measures and physiological events in the pharyngeal phase of swallowing between PD and controls and (2) analysing the association between tongue pressure and LVC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In addition, there are few reports of studies on tongue endurance compared with tongue strength. Although there have been reports suggesting an association between decreased anterior tongue endurance and delayed laryngeal vestibular closure, the relationship between tongue endurance and swallowing function remains unclear ( 33 ). Investigating the effects of reduced muscle strength and endurance on swallowing efficiency and safety for the anterior and posterior portions of the tongue, respectively, could clarify whether tongue pressure is a clinical marker for the presence or absence of dysphagia and the pathophysiology of PD.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, there are few reports of studies on tongue endurance compared with tongue strength. Although there have been reports suggesting an association between decreased anterior tongue endurance and delayed laryngeal vestibular closure, the relationship between tongue endurance and swallowing function remains unclear ( 33 ). Investigating the effects of reduced muscle strength and endurance on swallowing efficiency and safety for the anterior and posterior portions of the tongue, respectively, could clarify whether tongue pressure is a clinical marker for the presence or absence of dysphagia and the pathophysiology of PD.…”
Section: Discussionmentioning
confidence: 99%
“…Solomon et al ( 30 ) investigated muscle strength and endurance in the tongue and hands of patients with PD and compared them with neurologically normal controls, and reported that the patients with PD had 8.3 kPa lower tongue strength and 8.2 s shorter endurance. Tongue strength can be measured in the anterior and posterior portions of the tongue, but studies of PD have reported declines in only the anterior portion or in both the anterior and posterior portions ( 32 , 33 ).…”
Section: Measurement Of Tongue Strengthmentioning
confidence: 99%
See 3 more Smart Citations